An overview: laser applications in dentistry - M. Jawad, Mohammed; Abdul Qader, Sarah T.; Zaidan, B. B.; Zaidan , A. A.; Abdul Qader, Ibraheem T.; Naji, Ahmed Wathik (Science Alert, 2011)
Dentistry has entered an exciting era of high technology. Lasers provide new powerful tools that is characterized by a bloodless field and applied in most branches of dentistry. There are many types of lasers, such as Gas laser, Chemical laser, Dye laser, Metal-vapor laser, Solid-state laser and Semiconductor laser. Each laser type has its own unique features, advantages and disadvantages. While one laser may be suitable for some procedures, it will be unsuitable for others, so it is important for the dentist to have a back ground information about this technology and its uses in dentistry.